2022
DOI: 10.3389/fmars.2022.862430
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Online Citizen Scientists and the Consensus Method to Monitor the Marine Biofouling Community

Abstract: Citizen science is an important and useful approach to research that broadens public science engagement and expands the scale at which science can be conducted. Monitoring for marine non-native species has been repeatedly identified as a venue for citizen scientists to make substantial contributions. In this study, we evaluated the accuracy of identifications made by volunteers of marine invertebrates on the project Invader ID, hosted on the online citizen science portal Zooniverse. We tested the efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Instead, in the task of detecting presence or absence of iguanas within an image, we found that the answer selected by five volunteers or more (from 20 or 30 total classifications) — which we refer to as the minimum threshold — was the most likely to be correct. This was somewhat unexpected, since previous work has shown that accuracy increased asymptotically with number of classifications per image (Swanson et al, 2016); however, other projects hosted by Zooniverse have found outcomes more similar to ours (Egna et al, 2020; Hennon et al, 2015; Lawson et al, 2022). We suspect that for some challenging images, highly skilled volunteers were required to identify the iguanas, and that these volunteers were relatively rare.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Instead, in the task of detecting presence or absence of iguanas within an image, we found that the answer selected by five volunteers or more (from 20 or 30 total classifications) — which we refer to as the minimum threshold — was the most likely to be correct. This was somewhat unexpected, since previous work has shown that accuracy increased asymptotically with number of classifications per image (Swanson et al, 2016); however, other projects hosted by Zooniverse have found outcomes more similar to ours (Egna et al, 2020; Hennon et al, 2015; Lawson et al, 2022). We suspect that for some challenging images, highly skilled volunteers were required to identify the iguanas, and that these volunteers were relatively rare.…”
Section: Discussionsupporting
confidence: 50%
“…This was somewhat unexpected, since previous work has shown that accuracy increased asymptotically with number of classifications per image (Swanson et al, 2016); however, other projects hosted by Zooniverse have found outcomes more similar to ours (Egna et al, 2020;Hennon et al, 2015;Lawson et al, 2022). We suspect that for some challenging images, highly skilled volunteers were required to identify the iguanas, and that these volunteers were relatively rare.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…For large datasets, confirmation by an expert reviewer may not be possible and in its absence, positive identification must be accepted once a certain level of consensus among non‐expert observers is achieved (Swanson et al, 2016). To reduce the chances of consensus being incorrect, the threshold set for the detection of a true recapture event using photo‐based CMR will need to be set based on the degree of variability in the target feature between individuals in the population, the size of the database, the number of participants who are used to compare all images, and verification tests on portions of the data (Lawson et al, 2022; Pennycuick, 1978; Swanson et al, 2016). We suggest that there are key aspects of the photographing process that are standardized, such as ensuring the camera lens is focused on the vein branches so that they are not blurry, and making sure tails are straight to prevent vein distortion.…”
Section: Discussionmentioning
confidence: 99%